Omega-3 Fatty Acids and Fecundation, Pregnancy and Breastfeeding - Politano, Carlos Alberto; López-Berroa, Jorge (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Long-chain omega-3 (n-3) polyunsaturated fatty acids (PUFAs), such as the eicosapentaenoic and docosahexaenoic acids, have been linked to human health in all stages of life, from fetal development to aging. These PUFAs act as precursors for various metabolites involved in the prevention of certain diseases. The recognizable effects of these supplements prior to pregnancy (oocyte maturation), during pregnancy (improvement in the risk of premature delivery, among others) and in the offspring (in terms of cognitive function and the approach to neurodevelopmental disorders) are described in the present narrative review. We concluded that the diffusion of these supplements may improve the prognosis of these patients in a simple, effective way, and with high safety rates.
Keywords: omega-3; eicosapentaenoic acid; docosahexaenoic acid; pregnancy; breastfeeding